Augmented reality integrated chatbot to improve learning outcomes in secondary school students. - Reno Nurdiyanto; Henry Praherdhiono; Made Duananda Kartika Degeng (Inovasi Kurikulum, 2024)
The major challenge in learning science is that it is abstract and complex for some students to understand. For example, elements and compounds cannot be seen directly in very micro-sized objects; therefore, visualizing this concept can be challenging. Another challenge is the limited time for teachers to answer questions, provide explanations, and provide feedback during the learning process. This study aims to develop augmented reality learning tools integrated with large language models in the format of a chatterbot text-to-text that can be utilized on the topic of elements and compounds. The development model that has been implemented is adapted from the Lee and Owen model, which includes need analysis, front-end analysis, design, development, implementation, and assessment. Media and content experts have assessed the technology's suitability for classroom learning for 8th-grade students of Salafiyah Junior High School in Pekalongan. Based on field implementation, this technology obtained a positive perspective and indicated an improvement in learning outcomes on element and compound topics. The integration of AR and ChatBot contributes significantly to the innovative classroom learning process and creates a learning experience that suits the needs of students in this digital era. AbstrakKendala utama dalam pembelajaran IPA yaitu abstrak dan sulit untuk dipahami oleh beberapa siswa. Contohnya konsep mengenai unsur dan senyawa yang tidak bisa dilihat dalam bentuk secara langsung dalam objek yang berukuran sangat kecil, sehingga memvisualisasikan konsep ini bisa menjadi tantangan. Tantangan lain berupa waktu yang terbatas untuk guru dalam siswa dalam menjawab pertanyaan, memberikan penjelasan, dan memberikan umpan balik selama proses pembelajaran. Studi ini bertujuan untuk mengembangkan media pembelajaran berupa augmented reality terintegrasi large language models dalam bentuk chatterbot teks ke teks sehingga dapat digunakan pada topik tentang unsur dan senyawa. Model pengembangan yang telah dilakukan diadaptasi model Lee dan Owen, yang meliputi analisis kebutuhan, analisis awal akhir, desain, pengembangan, implementasi, dan penilaian. Ahli media dan ahli materi telah menyatakan kelayakan untuk digunakan dalam pembelajaran kelas pada siswa kelas 8 SMP Salafiyah Pekalongan. Berdasarkan implementasi lapangan, teknologi ini memperoleh perspektif yang positif dan menunjukkan adanya peningkatan hasil belajar pada materi unsur dan senyawa. Integrasi dari AR dan Chatbot memberikan kontribusi signifikan bagi sebagai media pembelajaran dalam proses pembelajaran kelas yang inovatif dan menciptakan pengalaman pembelajaran yang sesuai dengan kebutuhan siswa di era digital saat ini.Kata Kunci: artificial intelligence; large language models; pembelajaran IPA; realitas berimbuh